Modeling of Ionization and Recombination Processes in Plasma with Arbitrary Non-Maxwellian Electron Distribution - Chengcai Shen; Xiaocan Li; Yuan-Kuen Ko; John C. Raymond; Fan Guo; Vanessa Polito; Viviane Pierrard (The Astrophysical Journal)
In astronomical environments, the high-temperature emission of plasma mainly depends on ion charge states, requiring accurate analysis of the ionization and recombination processes. For various phenomena involving energetic particles, non-Maxwellian distributions of electrons exhibiting high-energy tails can significantly enhance the ionization process. Therefore, accurately computing ionization and recombination rates with non-Maxwellian electron distributions is essential for emission diagnostic analysis. In this work, we report two methods for fitting various non-Maxwellian distributions by using the Maxwellian decomposition strategy. For standard κ -distributions, the calculated ionization and recombination rate coefficients show comparable accuracy to other public packages. Additionally, our methods support arbitrary electron distributions and can be easily extended to updated atomic databases. We apply the above methods to two specific non-Maxwellian distribution scenarios: (i) accelerated electron distributions due to magnetic reconnection revealed in a combined MHD–particle simulation; and (ii) the high-energy truncated κ -distribution predicted by the exospheric model of the solar wind. During the electron acceleration process, we show that the ionization rates of high-temperature iron ions increase significantly compared to their initial Maxwellian distribution, while the recombination rates may decrease due to the electron distribution changes in low-energy ranges. This can potentially lead to an overestimation of the plasma temperature when analyzing the Fe emission lines under the Maxwellian distribution assumption. For the truncated κ -distribution in the solar wind, our results show that the ionization rates are lower than those for the standard κ -distribution, while the recombination rates remain similar. This leads to an overestimation of the plasma temperature when assuming a κ -distribution.